Comparing natural area herbicides for residual weed control and native species tolerance - Clark, Shannon, author; Sebastian, Derek, author; Nissen, Scott, author; Sebastian, Jim, author (Colorado State University. Libraries, 2017)
Downy brome (Bromus tectorum L.) is a competitive winter annual grass species, and is considered one of the most problematic invasive species on rangeland, open spaces and natural areas, and sites impacted by fire. Downy brome seeds germinate in the late summer or fall, overwintering until the seedlings begin rapidly growing in the spring, exploiting available water and nutrients before native grasses and forbs have emerged from dormancy. Invasive winter annual grasses, including downy brome, pose a major threat to native ecosystems by increasing fire frequency and intensity, degrading available wildlife and pollinator habitat, and decreasing native species diversity. Dalmatian toadflax (Linaria dalmatica L.) is another problematic invasive weed species found in dense populations in the western US, many times co-occurring with downy brome. Dalmatian toadflax infestations can be hard to control and the weed easily outcompetes native vegetation. The currently recommended herbicides (aminocyclopyrachlor, imazapic, picloram) for restoration of sites with invasive annual grasses and other biennial and perennial weeds have proven to provide inconsistent control or cause injury to desirable perennial species. Indaziflam, a new herbicide alternative for weed management in natural areas and open spaces, has been proven to provide long-term control of downy brome and other weed seedlings. A field trial was conducted to evaluate native species tolerance to indaziflam and other currently recommended herbicides used for downy brome and Dalmatian toadflax control. A total of 11 herbicide treatments were applied at two separate locations. For each native species, total counts were conducted across the entire plot area and analyzed as an increase or decrease compared to the non-treated control plots. Species richness was calculated by comparing the amount of unique species in each plot to the non-treated plots. Downy brome control, Dalmatian toadflax control, and perennial grass response were also evaluated through visual evaluations. Only indaziflam treatments (44, 73 and 102 g∙ai∙ha-1) increased native species richness (up to 8%, ± 1.2% SE) while providing 95-100% downy brome control. Imazapic treatments provided limited downy brome control and failed to increase species richness compared to non-treated plots. Aminocyclopyrachlor and picloram treatments resulted in a significant reduction in species richness, with up to a 35% decrease ± 1% SE compared to non-treated plots. Treatments containing picloram plus indaziflam provided significant control of Dalmatian toadflax compared to picloram alone, suggesting indaziflam provides extended control of the weed seedlings. These results suggest that indaziflam could be used by land managers as an alternative herbicide treatment, with less impact to native species, in restoring open spaces and natural areas severely impacted by downy brome and other invasive weed species. Additional work on the impact of herbicides to native species is needed to determine management options for restoration of native habitats. Future work includes conducting tolerance studies at sites where native species are grown in a production setting to reduce variability in species occurrence. Additionally, research looking at the impact of other weed management options, such as burning, to the native plant community is necessary for determining best management practices for restoration.
065 - Shannon Lee Clark
Comparing herbicides for residual weed control and native species tolerance
Keywords: downy brome; indaziflam; cheatgrass; natural areas; herbicide; species richness; species tolerance